The Physical Activity During Pregnancy: Recommended and Contraindicated Sports - Mruzek, Hanna; Głowacka, Barbara; Wesołowska, Aleksandra; Jasak, Paulina; Kania-Bonicka, Zofia; Owczarek, Sandra; Żółtowska, Marta; Sobótka, Aleksandra; Kałwak, Oliwia; Dziechciarz, Oriana (Quality in Sport, 2026)
Background. Despite growing evidence supporting the safety and benefits of exercise in pregnancy, pregnant women and their healthcare providers frequently lack clear guidance on which specific sports are safe, which require modification, and which should be avoided. Aim. This narrative review synthesizes current evidence on physical activity during pregnancy, with focus on classifying specific sports as recommended, conditionally permitted, or contraindicated, and on providing trimester-specific recommendations. Material and Methods. A structured search of PubMed/MEDLINE, Scopus, and Web of Science was conducted, covering publications from January 2010 to January 2025. Results. Regular moderate-intensity physical activity reduces the risk of gestational diabetes, excessive weight gain, hypertensive disorders, and prenatal depression. Walking, swimming, stationary cycling, prenatal yoga, Pilates, and moderate resistance training are safe across all trimesters. Contact sports, scuba diving, high-altitude exercise, hot yoga, and maximal-intensity exertion constitute absolute or relative contraindications. Recreational running and tennis may be continued with progressive modification by previously active women. Conclusions. Physical activity in pregnancy is safe and beneficial when appropriately selected and adapted to each trimester. Current guidelines converge on general principles but lack sport-specific detail. This review provides a clinically applicable, evidence-based classification of individual sports within a trimester-sensitive framework.